Incidence and Susceptibility of Uropathogens Isolated among the Patients at Tertiary Care Hospital in Eastern Nepal - Chaudhari, Bigu Kumar; Singh, Ganesh Kumar; Parajuli, Kamal Prasad; Shrestha, Kewal (Journal of Nobel Medical College, 2016)
Background Urinary Tract Infection (UTI) is one of the most common infectious diseases which affect almost all ages groups of population. Production of â-lactamases is responsible for antibacterial resistance which is frequently observed in Enterobacteriaceae isolates, particularly by E. coli and Klebsiella pneumoniae. This investigation has been carried out to determine the current status of prevalence and susceptibility of uropathogens isolated among the patients at tertiary care hospital in eastern Nepal.Material and Methods This study was done at the department of Microbiology, Nobel Medical College Teaching Hospital, Biratnagar, Nepal during May 1st 2015 to October 31st 2015. Midstream cleancatch urine was sampled from 1730 suspected urinary tract infection patients of different age and sex groups. Uropathogens were recognized in term of standard and specific microbiological techniques and antimicrobial susceptibility pattern was determined by Kirby Bauer Disc diffusion method following Clinical and Laboratory Standards Institute (CLSI) guidelines.Results Out of 1730 suspected specimens Culture resulted a total of 761 (43.98 %) positive and 969 (56.02%) negative among that significant growths of uropathogens including 700 (91.98 %) unimicrobial and 60 (7.88 %) polymicrobial growths. In term of Gender distribution 443 (25.60 %) were male and 1287 (74.40 %) were female hence the ratio is 0.34:1, respectively. E. coli was the leading isolate (66 %), followed by Klebsiella spp. (12 %), Enterococcus spp. (8 %), Pseudomonas spp. (6 %), Acinetobacter anitratus (5 %), Proteus spp. (3 %).Conclusion The high frequency of multidrug resistance in bacterial uropathogens was seen. Principally, resistance patterns were seen higher for amoxycillin, co-trimoxazole, flouroquinolones and third-generation cephalosporins, Existing uropathogens highlights the highest rate of vulnerability to nitrofurantoin, amikacin and gentamicin which provide much better antibiotic coverage and can be adapted for practical treatment of urinary tract infections.  Journal of Nobel Medical College Vol.5(2) 2016; 51-55